ADAR1: a promising new biomarker for esophageal squamous cell carcinoma?. Issue 8 (August 2014) - Qiao, Jun-Jing; Chan, Tim Hon Man; Qin, Yan-Ru; Chen, Leilei
<x xml:space="preserve">Abstract</x> Esophageal Squamous Cell Carcinoma (ESCC) is a heterogeneous tumor with enormous genetic and epigenetic changes. RNA editing is an epigenetic mechanism that serves as an additional layer of 'RNA mutations' in parallel to DNA mutations. The most frequent type of RNA editing, A-to-I (adenosine-to-inosine) editing catalyzed by Adenosine DeAminase that act on RNA (ADARs), modulates RNA transcripts with profound impact on cellular functions. RNA editing dysregulation has been found to be associated with cancers. Our recent study demonstrated that among all the three RNA editing enzymes, only ADAR1 was overexpressed in primary ESCCs compared with matched non-tumor specimens. In this review, we will discuss current views on the involvement of abnormal A-to-I editing in cancer development, more specifically on the ADAR1-mediated editing in ESCC. Although much is not yet learned about the role of ADAR1 in ESCC, ADAR1 may present an attractive option as a new biomarker for ESCC and as a new molecular therapeutic target.